Improving the Professional Competence of Teachers through Learning Communities - Arifin; Bestari Laia; Ni Luh Ika Windayani; Lies Dian Marsa Ndraha; Ni Wayan Risna Dewi; Jean Imaniar Djara; Imam Subayil (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study explores community activities that contribute to enhancing teachers' professional competence. Employing a qualitative approach, data were collected through interviews, observations, and documentation and analyzed using the interactive model of Miles and Huberman, encompassing data collection, analysis, and reporting. Findings reveal that learning communities within schools significantly support teachers’ learning processes and foster improvements in their professional competencies, evident in their teaching practices, material delivery, and commitment to the profession. The study underscores the importance of learning communities as platforms for sharing best practices, deepening content knowledge, enhancing pedagogical skills, and developing innovative teaching strategies—thereby cultivating a culture of professionalism and lifelong learning. Furthermore, the research contributes to the development of a collective-based professional development model that prioritizes collaboration over individual training, which often lacks sustained impact. Lastly, learning communities are shown to foster a sense of belonging and support among teachers, increasing motivation, self-confidence, and willingness to experiment with new approaches. This research thus strengthens the implementation of the Merdeka Curriculum by promoting collaborative and sustainable professional development for teachers. Keywords: Teacher Competency, Learning Community, Teacher Professional Competence